Understanding the Drivers of Food Waste in Malaysian Public Hospitals (MyHoFWa Study) - Nurul Alia Aqilah Samiun; Nurul Huda Razalli; Suzana Shahar; Zahara Abdul Manaf; Zurina Kefeli@ Zulkefli; Norshariza Jamhuri (Penerbit Universiti Sains Malaysia, 2026)
Tier 2- Indexed by WOS/SCOPUS